First progress report on the Japan Endoscopy Database project. Issue 1 (9th November 2017) - Kodashima, Shinya; Tanaka, Kiyohito; Matsuda, Koji; Fujishiro, Mitsuhiro; Saito, Yutaka; Ohtsuka, Kazuo; Oda, Ichiro; Katada, Chikatoshi; Kato, Masayuki; Kida, Mitsuhiro; Kobayashi, Kiyonori; Hoteya, Shu; et al.
Abstract : Background and Aim: The Japan Endoscopy Database (JED) Project was started to develop the world's largest endoscopic database, capture the actual performance of endoscopic practice, and standardize the terminology and fundamental items needed for a clinical and research registry. This paper presents a progress report on the first phase of this project undertaken at eight endoscopic centers in Japan. Methods: The list of data items to be collected was drafted by the MSED‐J (Minimal Standard Endoscopic Database) subcommittee. These items were aggregated offline by integrating data from two endoscopic filing systems between July 2015 and December 2015. The study population included all patients who underwent esophagogastroduodenoscopy or colonoscopy at all eight centers, patients who underwent enteroscopy at five of the eight centers, and patients who underwent endoscopic retrograde cholangiopancreatography (ERCP) at four of the eight centers. Results: Data collected in this phase included 61 070 endoscopic procedures, of which 40 475 were esophagogastroduodenoscopies, 215 were enteroscopies, 19 204 were colonoscopies, and 1176 were ERCPs. Frequencies of complications were 0.68% for esophagogastroduodenoscopy, 0% for enteroscopy, 0.43% for colonoscopy, and 13.34% for ERCP. In addition, we obtained various data including Helicobacter pylori infection status, past history of endoscopy in patients who underwent enteroscopy or colonoscopy, and degree of difficulty of ERCP, although the frequencies of reporting were sometimes low, with some items <20%. Conclusion: Results of the first phase suggest that the JED project can provide vast quantities of useful data about endoscopic procedures.